2012
DOI: 10.1103/physrevb.86.085407
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioinvestigation of defect formation at ZrO2-CeO2interfaces

Abstract: The structural and electronic properties of low index (100) and (111) ZrO 2 -CeO 2 interfaces are analyzed on the basis of density functional theory calculations. The formation energy and relative stability of substitutional defects, oxygen vacancies, and vacancy-dopant complexes are investigated for the (100) orientation. By comparing these results with the ones obtained in bulk structures, we provide a possible explanation for the higher experimental ionic conductivity measured at the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…22,23 Similarly, recent density functional theory calculations performed on a CeO 2 /ZrO 2 junction, predicted lower oxygen vacancy formation energy at the interface (due to the strain state) than in the bulk (from 2.80 eV in bulk to 0.50 eV at the interfacial plane of CeO 2 ). 24 Nonetheless, as shown in Figure 5, the Ce-M 5 /M 4 intensity ratios collected from regions of the sample with different strain fields (compressive vs. tensile) as well as from a partially strain-relaxed 5 nm thick film are identical. This suggests that misfit strain is not the predominant factor in determining the Ce 3+ enrichment at the interface.…”
mentioning
confidence: 75%
“…22,23 Similarly, recent density functional theory calculations performed on a CeO 2 /ZrO 2 junction, predicted lower oxygen vacancy formation energy at the interface (due to the strain state) than in the bulk (from 2.80 eV in bulk to 0.50 eV at the interfacial plane of CeO 2 ). 24 Nonetheless, as shown in Figure 5, the Ce-M 5 /M 4 intensity ratios collected from regions of the sample with different strain fields (compressive vs. tensile) as well as from a partially strain-relaxed 5 nm thick film are identical. This suggests that misfit strain is not the predominant factor in determining the Ce 3+ enrichment at the interface.…”
mentioning
confidence: 75%
“…The use of epitaxial strain induced in a thin film by lattice mismatch with a substrate has been intensively studied for control of oxygen migration and the formation of oxygen defects in binary oxides [80,81,82,83,110,111,112,113,114] and ABO 3 perovskite oxides [7,85,86,115,116,117,118,119]. Theoretical studies [110,112] have shown that tensile (compressive) strain can decrease (increase) the formation energy of oxygen vacancies in CeO 2 .…”
Section: Control Of Oxygen Migration In Rp Oxidesmentioning
confidence: 99%
“…However, their studies did not consider the position of defect levels in the GaAs relative to the ZrO 2 band gap. The impact of native defect on device performance is still a subject of much debate [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%